Seytniyazovlardıń poemalarında anadiplosislerdiń kórkemlik xızmeti - Sayımbetov, Sh.U. I.Yusupov hám M (SCIENCE and SOCIETY, 2025)
The article examines the method of repetition of anadiplosis. Theoretical provisions of anadiplosis are
Keywords: poem; anadiplosis; artistic task; lyrical hero; objective hero; word intonation; emotion